The first wave of B lymphopoiesis develops independently of stem cells in the murine embryo. Issue 1 (26th February 2015) - Yoshimoto, Momoko
Abstract : In the developing mouse embryo, there are several waves of hematopoiesis. Primitive and definitive erythromyeloid lineages appear prior to hematopoietic stem cell (HSC) emergence, and these waves are considered to be transient and support embryonic homeostasis until HSC‐derived hematopoiesis is established. However, recent evidence strongly suggests that HSC‐independent immune cells, such as tissue macrophages and some innate lymphoid cells, develop in the mouse embryo and persist into postnatal life. Innate type B‐1 cells have also been reported to emerge from hemogenic endothelial cells in the extraembryonic yolk sac and para‐aortic splanchnopleura, and continue to develop in the fetal liver, even in HSC‐deficient mouse embryos. Here, this review discusses B‐1 cell development in the context of the layered immune system hypothesis of B lymphopoiesis and the emergence of B‐1 cells independent of HSCs.